2020
DOI: 10.3390/su12072685
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Using Recharge Wells for Controlling the Saltwater Intrusion in Unconfined Coastal Aquifers with Sloping Beds: Numerical Study

Abstract: Groundwater systems are considered major freshwater sources for many coastal aquifers worldwide. Seawater intrusion (SWI) inland into freshwater coastal aquifers is a common environmental problem that causes deterioration of the groundwater quality. This research investigates the effectiveness of using an injection through a well to mitigate the SWI in sloping beds of unconfined coastal aquifers. The interface was simulated using SEAWAT code. The repulsion ratios due to the length of the SWI wedge (RL) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…The results confirmed that the SWI interface tip depended on the bed geometry layer [49]. Armanuos et al (2020) utilized SEAWAT to explore the consequence of using freshwater recharge out of underground wells for controlling the SWI in unconfined sloped aquifers [33]. A sensitivity examination was accomplished to investigate the effect of changing the aquifer bed slope and hydraulic parameters on the repulsion ratio of SWI.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The results confirmed that the SWI interface tip depended on the bed geometry layer [49]. Armanuos et al (2020) utilized SEAWAT to explore the consequence of using freshwater recharge out of underground wells for controlling the SWI in unconfined sloped aquifers [33]. A sensitivity examination was accomplished to investigate the effect of changing the aquifer bed slope and hydraulic parameters on the repulsion ratio of SWI.…”
Section: Introductionmentioning
confidence: 75%
“…Several studies have suggested different strategies for preventing or controlling the SWI in coastal aquifers [22][23][24][25]. These methods can be summarized as the following measures: (i) a decrease in groundwater abstraction [26,27], (ii) artificial recharge through recharge wells and spreading basins [28,29], (iii) freshwater injection in the coastal area to maintain the freshwater ridge [30][31][32][33], (iv) abstraction of saltwater along the coast [34,35], (v) construction of underground barriers [36,37], (vi) optimization of the rate of abstraction [38][39][40], (vii) land reclamation, and (viii) a combination of different techniques [41,42]. These approaches are described in the following paragraphs.…”
Section: Introductionmentioning
confidence: 99%
“…Seawater intrusion in coastal aquifers is a worldwide problem caused, among other factors, by aquifer overexploitation related to human activities, such as irrigation and drinking water supply, and the reduction in natural groundwater recharge due to climate change [1]. To prevent or limit the deterioration of both surface water and groundwater quality due to salt-water contamination, research studies have been developed to fully comprehend the problem and identify its fundamental parameters, as well as to evaluate possible countermeasures, such as cut-off walls (e.g., [2][3][4][5][6][7][8][9][10][11][12]).…”
Section: Introductionmentioning
confidence: 99%
“…The object of most previous GDCSI research has comprised simple hypothetical examples, and the contamination source has always been of a simple design and generalized as a point (Mo et al, 2019;Xing et al 2019;Armanuos et al, 2020;. In addition, previous GDCSI was not comprehensive enough, and identification of shape of contamination source was rarely considered.…”
Section: Introductionmentioning
confidence: 99%